Emancipatory spaces in the post-colony : South Africa and the case for AbM and UPM,Emancipatory spaces in the post-colony South Africa and the case for Abahlali Shackdwellers Movement and the Grahamstown based Unemployed Peoples Movement - Tselapedi, Thapelo (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2012)
This thesis is about the relationship between local government, grassroots organisations and the organisation of power resulting from the interaction of the two. Exploring this relationship this thesis investigates whether the actions of grassroots movements can bring local government in line with their developmental role as accorded to them by the Constitution. The assumption embedded in this question is that the current balance of power at the local level exists outside of the service of the historically disadvantaged. Following on from that, the thesis explores, through different modes of analysis, theoretical and historical, the policy and constitutional framework for local government, and then it unravels the context set by the political economy of South Africa. The aim is to make a significant attempt at understanding the possible implications of the interventions grassroots movements make in the public space. The thesis does this also by looking at the strengths and weaknesses of the strategies of the UDF to makes an assessment of the possible endurance of post-apartheid grassroots movements. Since civil society 'suffers' from nationalist politics, with its own corporatist institutions, the thesis searches deep within or arguably 'outside of civil society', subjecting AbM and UPM to academic critique, to see how movements embedded among the poor and carrying the political instrument of anger and marginalisation, can dislodge the power of capital. More importantly, the thesis situates the post-apartheid moment within postcolonial politics; navigating through the legacy of Colonialism of a Special Type (CSP), the thesis explores the limits and opportunities at the disposal of grassroots movements. From a different perspective, the thesis is an examination of the organisation and movement of power and the spaces within which power and ideas are contested. Drawing on the political and economic engagements, dubbed the Dar Es Salaam debates, in the 1970's and 1980's spurred on by Issa Shivji, the late Prof Dani Wadada Nabudere and Mahmood Mandani, the conclusions of this thesis develops these engagements, essentially making a case for the continued centrality of the post-apartheid state. However, the thesis also asserts the indubitable role that both grassroots movements and civil society need to play, not necessarily in the democratisation of the state, though that goes without saying, but in taking the post-colonial state on its own terms. Consequently, the thesis puts forward the idea that issue-based mobilisation does exactly this, and in the manner that acknowledges the state's centrality and makes paramount the self-organisation (popular assemblies) of ordinary people in public affairs. The thesis categorically concludes that the centrality of the post-apartheid state and its progressive outlook (constitutional values) is contingent on organs of popular assemblies which need to take the state on its (progressive) terms.
Keywords: Local government -- South Africa -- Grahamstown; Postcolonialism -- South Africa -- Grahamstown; Apartheid -- South Africa; Civil society -- South Africa -- Grahamstown; Social movements -- South Africa -- Grahamstown; South Africa -- Economic conditions -- 1991-; South Africa -- Economic policy; South Africa -- Politics and government -- 1994-